Glassy-Winged Sharpshooters Cease Feeding and Avoid Plants Treated With Sub-Lethal Doses of the Neonicotinoid Insecticide Imidacloprid - Sisterson, Mark S.; Uchima, Sean Y.; Wallis, Christopher M.; Krugner, Rodrigo (Journal of economic entomology, 2023)
Insecticides are a primary means for suppressing populations of insects that transmit plant pathogens. Application of insecticides for limiting the spread of insect-transmitted plant pathogens is often most effective when applied on an area-wide scale. The glassy-winged sharpshooter is a vector of the bacterial pathogen Xylella fastidiosa, which causes numerous plant diseases including Pierce's disease of grapevine. The glassy-winged sharpshooter has been the subject of an area-wide suppression program in California for nearly two decades. Overreliance on a limited number of active ingredients including the neonicotinoid imidacloprid has resulted in increased levels of resistance to commonly applied products. In California, glassy-winged sharpshooters move between citrus, an important overwintering host, and vineyards. Accordingly, imidacloprid is routinely applied via the irrigation system in vineyards and citrus orchards. For soil applied applications, it may take days to weeks for concentrations in plants to increase to lethal doses. Further, as the dose of imidacloprid required to kill sharpshooters increases due to resistance, so too does the period that sharpshooters are exposed to sub-lethal doses. Response of glassy-winged sharpshooter to cowpea plants treated with sub-lethal doses of imidacloprid was evaluated by conducting no-choice and choice tests. In no-choice feeding assays, glassy-winged sharpshooters caged on plants treated with sub-lethal doses of imidacloprid ceased feeding and produced little excreta. Further, sub-lethal exposure to a range of doses over a 4-d period did not affect viability over a 9-wk post-exposure holding period on untreated plants. In choice-tests, glassy-winged sharpshooters avoided treated plants and were observed predominately on untreated plants. Results suggest that application of imidacloprid to vineyards and citrus orchards may push glassy-winged sharpshooters out of treated habitats rather than kill them.